2014
DOI: 10.14432/j.macvetrev.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes of Lymphoid Tissue in the Harderian Gland of Laying Hens

Abstract: The Harderian gland of 110 laying hens was histologically investigated from the time of hatching to the period of 10 months of age. Tissue sections were stained with haematoxylin and eosin, periodic acid-schiff (PAS) and methyl green-pyronin technique. The research shows that lymphoid tissue is colonised by three types of cells: heterophils, lymphocytes and plasma cells. The number of these cells is directly dependent on the bird’s age. During the lifetime of the hens there gradually comes a shift in the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
2
8
0
1
Order By: Relevance
“…In our previous studies we observed the enlarged lymphoid tissue in the harderian gland of vaccinated chickens compared to the non-vaccinated ones . Our results confi rm the data, stating that lymphoid nodules of the harderian gland are not observed in the chickens up to the age of 40 days (Bejdic P et al, 2014.…”
Section: Discussionsupporting
confidence: 91%
“…In our previous studies we observed the enlarged lymphoid tissue in the harderian gland of vaccinated chickens compared to the non-vaccinated ones . Our results confi rm the data, stating that lymphoid nodules of the harderian gland are not observed in the chickens up to the age of 40 days (Bejdic P et al, 2014.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present study regarding presence of intense PAS positive activity in the plasma cells and Russell bodies in the interstitial connective tissue of the Harderian gland at 17 and 24 days of age ( Fig 5) coincides with the observations reported by W ight et al (1971) in domestic fowl and Bejdic et al (2014) in laying hens.…”
Section: Histochemical Changes During Development Of Harderian Gland supporting
confidence: 93%
“…The fowl HG has a large agedependent populations of plasma cells and is capable to produce antibodies both to systemically and locally applied antigens (Burns, 1992). The plasma cells of HG produce or participate in the transmission of four classes of immunoglobulins: IgA, IgG, IgM and IgY (Ohshima & Hiramatsu, 2002;Bejdic et al, 2014).…”
Section: Introductionmentioning
confidence: 99%